Juror comprehension and complexity. Strategies to enhance understanding - Findlay, Mark (The British journal of criminology, 2001)
Recent law reform debate proposes the complexity of trials as generally reducing juror comprehension. This in turn is said to impact on the accuracy of the verdict. The empirical studies of three very different jury systems examined in detail in the paper challenge these assumptions against problematic measures of complexity. Critics of the jury, particularly in commercial fraud trials, often take the issue of trial complexity as a given. The studies demonstrate that features of the trial which trouble jurors in terms of concentration, comprehension and decision making are consistent, while often specific to the trial and interrelated. The paper argues for a more sophisticated analysis of trial complexity to precede further empirical testing of the relationship between complexity, comprehension and verdict delivery. This is crucial as a foundation for any policy reform regarding verdict delivery mechanisms on the basis of trial complexity